Design and development of end effector for changing bulb - Khazani M.M.M.; Jalal M.F.A.; Isa M.R.; Sahari K.S.M. (American Institute of Physics Inc., 2023)
Replacing a light bulb is a common household task to be done regularly. Existing bulb changer products on the market, however, can be difficult for the elderly and weak people to use. In this paper, a bulb changer device is designed and developed to help ease people at home doing their household tasks. The device incorporates some of the existing ideas with significant improvement by introducing some sort of automation system. An end effector is designed and developed to be a semi-automated spring gripper. The result shows that the device can perform the essential task of changing a light bulb. The maximum reach attained by the device with extension pole attached is within the range of common ceiling heights of 3 to 4m. The maximum spread of the gripper is below 135mm, meaning that the device can fit into the bulb housing. The overall performance speed is fairly slow but acceptable. 2019 Author(s).